Semantic Ontologi Sebagai Solusi Potensial untuk Meningkatkan Interoperabilitas Data - Rahmi Nur Shofa; I Made Oka Widyantara (Prosiding SISFOTEK, 2025)
Digital transformation requires a modern management information system (MIS) to integrate data originating from various subsystems with heterogeneous formats, terminology and structure. Conventional schema mapping and extraction-transformation-load (ETL) based approaches are often incapable of addressing these challenges semantically. Semantic Ontologies offer conceptualization solutions that support interoperability and enable automated reasoning. This article presents a comprehensive understanding of the current literature on the application of semantic ontologies to information systems, highlighting the main contributions and limitations of previous research. The results show that most research still focuses on specific domains (culture, education, business), while semantic transmission across enterprise subsystems, ontology evolution issues, and performance evaluation measures are still rarely researched. Based on this mix, this research offers a semantic ontology framework designed for holistic data representation in integrated MIS, with the emphasis of ontology development across subsystems (ERP, CRM, SCM, HRIS), as well as performance evaluation measured in the aspects of interoperability, reasoning and query efficiency. It is hoped that this information contribution can strengthen the destruction of management systems while increasing the organization's adaptability to digital business dynamics.